Last Mile Delivery for e-Commerce: A Model Approach and Current Trends - Joanna DROBIAZGIEWICZ (Communications of International Proceedings, 2021)
The aim of the article is to present fills the gap in the literature regarding a different view of the theoretical last mile delivery model and the compilation and synthetic characteristics of various practical models for e-commerce in the B2C sector. The article also presents a practical example of the last mile delivery organization of a company that uses the omnichannel strategy. It points to possible ways to optimize delivery activities during the significant development of e-commerce, which is related, among others, to the Covid -19 pandemic. The article uses the method of critical analysis of source literature and case study. The conducted research indicates the necessity to change the existing distribution management model of the surveyed company, whose share of electronic sales in total sales is increasing. It is important to remodel the distribution center, modify the existing IT systems and change the goods allocation strategy (multichannel stock management), as well as develop the last mile form of delivery, parcel local collection points and parcel lockers, which are popular with customers. Based on a critical analysis of the literature, the first part of the article presents the essence of the last mile delivery and a proposal of its model. Current trends in last mile logistics are also described. In the next part, on the basis of the previous considerations, e-commerce last mile delivery models used in practice were distinguished and their characteristics were presented. In the practical part, the model used in a selected company is described and the directions of activities improving the last mile in connection with the growing sales of e-commerce are indicated. The last part of the article presents conclusions from the research.
Keywords: e-commerce; last mile; delivery logistics.